KONTRIBUSI ZAKAT TERHADAP PEREKONOMIAN: SYSTEMATIC LITERATURE REVIEW - Nisa Khairunnisa; Ismail Ismail; Nur Imamah; Ririn Dwi Aryanti; Sukardi Sukardi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to address the research question on the development of the research topic regarding the contribution of zakat to the economy over the last 10 years, from 2014 to 2023. The method employed is Systematic Literature Review (SLR) with the application of VOSviewer. The review includes 85 articles sourced from the Scopus database. The findings reveal that the evolution of research on the contribution of zakat to the economy is closely related to the social, religious, and economic context of the country, particularly Indonesia, with a majority Muslim population. The existence of zakat institutions, such as BAZNAS and local zakat institutions, adds complexity to research in Indonesia. Conversely, countries with minority Muslim populations, such as Thailand and Japan, tend to have limited research on this topic. Zakat is not only viewed as a religious obligation but also as a strategic tool to support economic growth, especially in developing countries with a majority Muslim population. Productive zakat programs in Indonesia, like the Pekanbaru Cerdas Program, contribute positively to the community's economy, despite facing challenges. During the Covid-19 pandemic, zakat through Islamic Social Finance serves as a solution in crisis recovery. Research findings emphasize the optimal role of zakat funds in addressing economic issues, with the distribution topic being the main focus and its derivatives such as Zakat Fund, programs, growth, economic growth, Covid, microfinance, and tax. This research contributes to a better understanding of the role of zakat in the economy, paving the way for more advanced thinking and effective policy implementation. The limitations of this study include the use of limited secondary data from Scopus. Future research should utilize primary data, including interview and observational data.